2015
DOI: 10.4269/ajtmh.14-0639
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Transmission of Opisthorchis viverrini sensu lato and a Lecithodendriid Trematode Species in Bithynia siamensis goniomphalos Snails in Northeast Thailand

Abstract: Abstract. Seasonal changes play roles in the transmission success of fish-borne zoonotic trematodes (FZT). This study examined the seasonal transmission patterns of Opisthorchis viverrini sensu lato (s.l.) and a virgulate cercaria (family Lecithodendriidae) in the snail intermediate host, Bithynia siamensis goniomphalos in northeast Thailand. Snail samples were collected monthly during the rainy, cool, and hot seasons during 2012-2013 to determine the prevalence and intensity of larval trematode infections. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…infections in Bithynia spp. from various standing-water habitats in northeastern Thailand, Cambodia, Lao PDR, and southern Vietnam were 1.39–3.04%, 0.0–6.8%, and 0.11–1.73%, respectively [ 7 , 9 , 17 , 27 , 28 , 30 , 32 , 35 , 59 ]. With respect to the populations living in these opisthorchiasis endemic areas, their lifestyles may be associated with higher-prevalence causes than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…infections in Bithynia spp. from various standing-water habitats in northeastern Thailand, Cambodia, Lao PDR, and southern Vietnam were 1.39–3.04%, 0.0–6.8%, and 0.11–1.73%, respectively [ 7 , 9 , 17 , 27 , 28 , 30 , 32 , 35 , 59 ]. With respect to the populations living in these opisthorchiasis endemic areas, their lifestyles may be associated with higher-prevalence causes than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The irrigated water from Nam Un dam finally joins with Songkram River before it drains into the Mekong River in Nakorn Phanon province. The rice paddy environment in SK is known to allow active transmission from human and animal reservoir hosts to Bithynia goniomphalos siamensis (Kiatsopit et al, 2012;Kopolrat et al, 2016;Namsanor et al, 2015). Whether different habitat types and/or other environmental attributes such as snail (Kiatsopit et al, 2013), fish and human hosts are responsible to the occurrence of this cryptic species in Sakon Nakhon is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, by using a multi-gene sequence approach (phylogenetic and (Kiatsopit et al, 2012;Namsanor et al, 2015). Currently it is not clear whether habitat ecology, connectivity and/or land use that encourages snail host population growth or a history of chemotherapeutic control by praziquantel has affected the genetic difference of the new SK isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent simulations incorporating these experimental data, as well as regional temperature and precipitation records, snail abundance and egg availability in the environment, provided a useful modeling framework to assess and predict seasonal transmission risk [24]. The model outputs suggested that transmission risk varies greatly over the year (see also [25,26]), with very low transmission risk during the dry season and increasing transmission risk at the onset of the rainy season (i.e. June–July) with a peak in September.…”
Section: Embracing Complexity For Liver Fluke Sustainable Controlmentioning
confidence: 99%